Pengaruh Kualitas Pelayanan Baskin Robbins melalui Online Foods terhadap Kepuasan Konsumen - Sugeng Santoso (PANDITA : Interdisciplinary Journal of Public Affairs, 2023)
The business world in Indonesia is increasingly experiencing changes that require business people to always improve their abilities. One of the changes in question is the change in the field of information technology. The current business process is not only done by visiting a shop or store, but can be done online through an application. In this study, the authors discussed the effect of Baskin Robbins' service quality through Online Foods on consumer satisfaction. Service quality is a measure of how well the level of service provided is capable or in accordance with customer expectations, with service quality indicators including reliability, responsiveness, assurance, empathy, and physical evidence. Meanwhile, consumer satisfaction is a cognitive purchase situation with respect to the equivalence or disproportion between the results obtained compared to the sacrifices made, with indicators of consumer satisfaction including conformity of expectations, willingness to repurchase, recommending, not paying attention to competing products, and willing to provide input. The research was conducted using associative descriptive, which is a method that analyzes and also describes/describes the variable data that was successfully obtained in the study and then draws conclusions, using a simple correlation coefficient technique. In this study it was concluded that 1) The average score of the service quality variable is 328, including good with indicators including reliability with a score of 367, responsiveness with a score of 294, assurance with a score of 350, empathy with a score of 318 and physical evidence with a score of 301 it can be concluded that the variable Quality of Service has been successfully carried out well 2) The average score produced on the variable consumer satisfaction is 345 and is in a good class interval; As for the indicators which include suitability of expectations with a score of 358, referential interest with a score of 316, , recommend with a score of 369, not paying attention to peeasing products with a score of 345, providing input to companies with a score of 339. So it can be concluded by researchers that the Baskin Robbins consumer satisfaction variable has worked well Good. 3) There is a strong positive influence given by service quality to customer satisfaction. The regression equation in this study is as follows: Y = 12.52 + 082 (X).